0069 Psychosocial Work Factors, Occupational Noise Exposure, Common Mental Disorders, and the Risk of Tinnitus. (23rd June 2014) - Winther Frederiksen, Thomas; Ramlau-Hansen, Cecilia H; Stokholm, Zara A; Vestergaard, Jesper M; Kolstad, Henrik A
Abstract : Objectives: Tinnitus is common, can be disabling, and may impair concentration, hearing and sleep. Noise induced hearing loss, other subtypes of hearing loss and ototoxic drugs are well-documented risk factors for tinnitus. Psychosocial work factors, depression and anxiety may exacerbate tinnitus, cause tinnitus, or both. The objective is to investigate the relationship between noise exposure, psychosocial work factors, common mental disorders, and tinnitus Method: A total of 554 workers within 10 manufacturing trades and children day-care participated in this cross-sectional study from 2009–2010. The study database contained information on individual short-term and long-term noise exposure levels, hearing levels and questionnaire information on common mental disorders and psychosocial work factors. Associations between noise exposure levels, hearing levels, depression, anxiety, burn-out symptoms, work-related stress and tinnitus will be analysed by use of multiple logistic regression analysis, taking a priori selected potential confounders into account. Results: Preliminary results show that of the 554 participants, 77% were males an the mean age was 43 years, ranging from 20–64 years. Among the participants, 17% reported tinnitus, 16% had a hearing handicap (WHO-definition), 3% anxiety disorder, 14% burn-out symptoms, 4% depression, and 8% reported work-related stress. Conclusions: Tinnitus is expected to represent a heterogeneous group of underlying disorders. We aim at contributing to a better understanding of the relative importance of the possible underlying factors in a population of occupationally noise exposed workers. Risk analyses are in progress, and results will be presented at the conference.